Happiness among Malaysian University students who stayed on campus during movement control order: What really matters? - Guan Teik Ee; Agnis Sombuling; Assis bin Kamu; Ho Chong Mun; Bradley T. Erford; Lei Mee Thien; Murnizam Halik (Springer nature link, 2025)
The happiness of 245 students who stayed on campus during the COVID-19 pandemic-induced Movement Control Order (MCO) at a public university in Malaysia was examined by comparing Subjective Happiness Scale scores from before the MCO to fve diferent time phases of the MCO. Happiness declined through MCO3, then increased back to pre-MCO levels. Factors that helped students sustain happiness levels during the MCO also were identifed. A one-way repeated measures ANOVA showed a signifcant time efect in happiness with a signifcant decline in happiness from before the MCO and the frst three MCOs. However, after MCO3, there was no further signifcant decline in happiness. Students reported that factors contributing to stability of happiness in social relationships were communication with friends and family; important infrastructure factors were quality Wi-Fi and café access; university support factors were money that students received and food supply, and important online teaching and learning factors were the e-learning platform and suitability of timing. Implications for counselling and organizational interventions are discussed.